Examining Teacher Support and Instructional Practices in Preschool Management: Evidence from Tanzania - Husna Juma Mlwale; Sisca Rahmadonna; Julius Jonas Mbawala (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
This study explored teacher support and instructional practices within preschool management in Tanzania and their implications for early childhood education quality. Guided by Vygotsky’s Social Constructivist Theory, the study employed a qualitative multiple-case design involving eight purposively selected participants (three headteachers and five preschool teachers) from three preschools. The sample size was determined based on the principle of information richness and thematic saturation rather than statistical representation. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that teacher support was limited and largely dependent on external initiatives, while instructional supervision focused primarily on administrative compliance rather than pedagogical improvement. Although teachers demonstrated knowledge of child-centered and play-based approaches, their implementation was constrained by overcrowded classrooms, inadequate teaching resources, and limited professional development opportunities. Interpreted through Vygotsky’s theory, these findings suggest that insufficient professional scaffolding from school leadership reduced teachers’ capacity to implement developmentally appropriate instructional practices. The study contributes to the literature by demonstrating that preschool management functions as the organizational mechanism linking teacher support and instructional practices within resource-constrained settings. The findings highlight the need to strengthen instructional leadership, institutionalize school-based teacher development, and increase investment in learning resources to improve preschool education quality